Indicative bioleaching of the sulphate of copper by means of microbial growth under conditions of mining drainage - Eyzaguirre Liendo, Paola del Rosario (2019)
The search for sustainable technological alternatives for acid mine drainage is a current necessity. The purpose of the study was to determine the bioleaching of copper sulphate by microbial growth under mining drainage conditions. From 2014 to 2015, the maximum average microbial production in leachates belonging to four dumps of the Toquepala mining site of the Southern Perú Copper Company was determined experimentally. Statistically significant differences (p <0.05) were found between the averages of the microbial activity in relation to the concentrations of the copper sulphate (0.0; 5.0; 10.0; 15.0; 20.0 g.L-1) where the results were (logarithm of cel/ml): 8.90±0.03; 7.77±0.06; 7.20±0.07; 7.04±0.04 and 7.00±0.02. It was concluded that the indicative bioleaching of copper sulphate was associated with microbiological growth as a technological process. However, it is necessary to establish experimental designs to determine those reactions that optimize microbial growth, and to guarantee greater contents of copper sulphate from the bioleaching.